Navigating complexity: Adaptive management in the Northern Karamoja Growth, Health & Governance program - and Allana, Amir (MercyCorps, 2014)
Development actors increasing agree that managing programs adaptively – especially complex interventions – can improve their effectiveness. But what does adaptive management look like in practice?
Keywords: IMPORTANT; Practice